Enablers of, and barriers to, optimal glove and mask use for routine care in the emergency department: an ethnographic study of Australian clinicians. (June 2020) - Barratt, Ruth; Gilbert, Gwendolyn L.; Shaban, Ramon Z.; Wyer, Mary; Hor, Su-yin
Abstract: Background: The risk of healthcare-acquired infection increases during outbreaks of novel infectious diseases. Emergency department (ED) clinicians are at high risk of exposure to both these and common communicable diseases. Personal protective equipment (PPE) is recommended to protect clinicians from acquiring, or becoming vectors of, infection, yet compliance is typically sub-optimal. Little is known about factors that influence use of PPE—specifically gloves and masks—during routine care in the ED. Methods: This was an ethnographic study, incorporating documentation review, field observations and interviews. The theoretical domains framework (TDF) was used to aid thematic analysis and identify relevant enablers of and barriers to optimal PPE use. Results: Thirty-one behavioural themes were identified that influenced participants' use of masks and gloves. There were significant differences, namely: more reported enablers of glove use vs more barriers to mask use. Reasons included more positive unit culture towards glove use, and lower perception of risk via facial contamination. Conclusion: Emerging infectious diseases, spread (among other routes) by respiratory droplets, have caused global outbreaks. Emergency clinicians should ensure that, as with gloves, the use of masks is incorporated into routine cares where appropriate. Further research which examines items of PPE independently is warranted.